Complexity and Choice - Yuval Salant; Jörg L. Spenkuch (Center for Economic Studies and ifo Institute (CESifo), 2021)
We study two dimensions of complexity that may interfere with individual choice. The first one is object complexity, which corresponds to the difficulty in evaluating any given alternative in a choice set. The second dimension is composition complexity, which increases when suboptimal alternatives become more similar to optimal ones. We develop a satisficing-with-evaluation-errors theory that incorporates both dimensions and delivers sharp empirical predictions about their effect on choice behavior. We confirm these predictions in a novel data set with information on hundreds of millions of decisions in chess endgames. First, as the object complexity of an optimal (suboptimal) alternative increases, it becomes less (more) likely to be chosen. Second, even highly experienced decision-makers are more likely to make mistakes when choosing from sets with higher composition complexity. These findings help to shed some of the first light on the effect of complexity on choice behavior outside of the laboratory.
Keywords: D91; 330; complexity; choice; satisficing; bounded rationality